CyDiv, a Conserved and Novel Filamentous Cyanobacterial Cell Division Protein Involved in Septum Localization - Mandakovic, Dinka; Trigo, Carla; Andrade, Derly; Riquelme, Brenda; Gómez-Lillo, Gabriela; Soto-Liebe, Katia; Díez, Beatriz; Vásquez, Mónica (Frontiers in Microbiology, 2016)
Cell division in bacteria has been studied mostly in Escherichia coli and Bacillus subtilis, model organisms for Gram-negative and Gram-positive bacteria, respectively. However, cell division in filamentous cyanobacteria is poorly understood. Here, we identified a novel protein, named CyDiv (Cyanobacterial Division), encoded by the all2320 gene in Anabaena sp. PCC 7120. We show that CyDiv plays a key role during cell division. CyDiv has been previously described only as an exclusive and conserved hypothetical protein in filamentous cyanobacteria. Using polyclonal antibodies against CyDiv, we showed that it localizes at different positions depending on cell division timing: poles, septum, in both daughter cells, but also in only one of the daughter cells. The partial deletion of CyDiv gene generates partial defects in cell division, including severe membrane instability and anomalous septum localization during late division. The inability to complete knock out CyDiv strains suggests that it is an essential gene. In silico structural protein analyses and our experimental results suggest that CyDiv is an FtsB/DivIC-like protein, and could therefore, be part of an essential late divisome complex in Anabaena sp. PCC 7120.